VECTOR DATA DIFFERENCES IDENTIFICATION IN THE THEMATIC PROCESSING OF SPACE IMAGES - A. A. Zalatoi; A. V. Urbanovich (Системный анализ и прикладная информатика)
The problem of differences identifying in vector graphics data packages and how to solve it is considered. Map information and vectorized data of remote sensing of Earth are sources of vector data in the article. The aim is to design a method for detecting differences in vector data packages, providing reliable results for updating map and monitoring areas tasks. Research and development is done by mathematical modeling of the task in MATLAB. The article provides developed method for solving the task and results of its application for finding differences between two vector data packages, obtained from the target information of remote sensing of the Earth, and/or vector layers of digital district map. This method allows you to automate the process and reduce the time of thematic analysis of cosmic information, obtained from remote sensing of the Earth for topographic mapping and monitoring areas.